2014
DOI: 10.1186/s13023-014-0206-5
|View full text |Cite
|
Sign up to set email alerts
|

Results from the French National Esophageal Atresia register: one-year outcome

Abstract: BackgroundThe aim of the present national prospective population-based study was to assess the early morbidity of esophageal atresia (EA).MethodsAll 38 multidisciplinary French centers that care for patients with EA returned a specific questionnaire about the 1-year outcome for each patient. This information was centralized, checked, and entered into a database.ResultsFrom the total population of 307 EA patients born in 2008 and 2009, data about the 1-year outcome were obtained from 301 (98%) patients, of whom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
68
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 15 publications
5
68
1
1
Order By: Relevance
“…8 Because of its rarity and complex nature, EA/TEF represents one of the major therapeutic challenges not only in modern pediatric surgery but also for other specialties involved due to serious short-and long-term morbidities. [13][14][15][16][17][18] Our results were consistent with previous studies indicating that despite precise esophageal reconstruction and excellent postoperative care, early and late complications frequently occur and must be dealt with. [19][20][21][22] The definition of possible complications is however lacking standardization, which makes an exact comparison with the literature difficult and thus results in highly variable incidence rates.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…8 Because of its rarity and complex nature, EA/TEF represents one of the major therapeutic challenges not only in modern pediatric surgery but also for other specialties involved due to serious short-and long-term morbidities. [13][14][15][16][17][18] Our results were consistent with previous studies indicating that despite precise esophageal reconstruction and excellent postoperative care, early and late complications frequently occur and must be dealt with. [19][20][21][22] The definition of possible complications is however lacking standardization, which makes an exact comparison with the literature difficult and thus results in highly variable incidence rates.…”
Section: Discussionsupporting
confidence: 94%
“…[19][20][21][22] The definition of possible complications is however lacking standardization, which makes an exact comparison with the literature difficult and thus results in highly variable incidence rates. 13,14 It can be assumed that the development of complications after initial EA/TEF repair is most likely a multifactorial process that depends on applied surgical techniques, peri-/postoperative care, and individual patient factors. 29 Early complications in our cohort included minor (6.3%) or major (5.2%) anastomotic leaks, recurrent TEF with (1.0%) or without (9.4%) anastomotic stricture, initially missed proximal fistula (4.2%) and refractory anastomotic strictures with (1.0%) or without (2.1%) fistula.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,3 Surgical necrotizing enterocolitis (NEC) increases the risk of poor growth at 18-22 months of age with respect to medical NEC. 2 Nutritional problems in neonates requiring gastrointestinal surgery are not unusual and nutritional support in these infants is often challenging.…”
mentioning
confidence: 99%
“…There were no changes in incidence, but with high mortality in total compared with developed countries (despite 100% survival during the last year) 17 21–23. The survival rate of esophageal atresia in developed countries has reached a plateau since 1980 and seems to be currently stable at around 95% 24. Pedersen et al 17 reported survival from 86.9% to 99.2% for esophageal atresia from 23 European countries in 1987–2006.…”
Section: Discussionmentioning
confidence: 99%